High brain - Ibrahim, Faridah Hanum; Mohd Moklas, Mohamad Aris; Ibrahim, Siti Aminah (Universiti Putra Malaysia Press, 2016)
Mitragyna speciosa or locally known as ketum in Malaysia is traditionally popular in the northern parts of Peninsular Malaysia and Thailand. The leaves are chewed or boiled and taken daily as a popular tonic by farmers to endure the sun, fatigue, and hard work. The truth is that ketum cheats the brain into believing that you are stronger than you thought.